The Ifiter program succeeded in fostering health awareness - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, March 17, 2023 - The I Fit and Eat Right (IFITER) program organized by the UMP Health Centre has succeeded in raising awareness among citizens concerned on health through healthy lifestyle practices and balanced nutrition.